Islamic Entrepreneurship as an Economic Pillar and Sustainability of UMKM - Marlisa, Tita Fidrya; Putri, Nadya Elmaliya (Yayasan Rahmat Islamiyah, 2025)
This research examis the role of Islamic entrepreneurship as an economic pillar and the sustainability of UMKM. The research method used is a metgod with a qualitative approach. The result showed that Islamic entrepreneurship can strengthen UMKM through ethical and social values. The conclusion of thus research is that Islamic entrepreneurship is an important pillar fir sustainabe economic development.